The role of brachytherapy for margin control in oral tongue squamous cell carcinoma - Ilia Ianovski; Alex M. Mlynarek; Martin J. Black; Boris Bahoric; Khalil Sultanem; Michael P. Hier (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The aim of this study is to assess the feasibility and effectiveness of using peri-operative brachytherapy (BRTx) for positive/narrow margins present post primary surgical resection of oral tongue squamous cell carcinoma (OTSCC). Methods Prospective single-centre study of patients with OTSCC (T1–3, N0–3, M0) treated with resection of primary tumour ± regional nodal resection and intra-operative insertion of BRTx catheters. BRTx was administered twice daily at 40.8Gy/12Fr for ‘Positive’ (≤2 mm) margins, at 34Gy/10Fr for ‘Narrow’ (2.1-5 mm) margins, and not given for ‘Clear’ (> 5 mm) margins over the course of 5–6 days, 3–5 days post operatively. Results Out of 55 patients recruited 41 patients (74.6%) were treated with BRTx, as 12 patients had clear margins and 2 patients had unfavourable tumour anatomy for catheter insertion. EBRTx was avoided in 64.3% of patients. Overall Survival (OS) at 3 and 5 years was 75.6 and 59.1% respectively, while Disease Specific Survival (DSS) was 82.3 and 68.6% at 3 and 5 years respectively. Recurrence and survival outcomes were not associated with margin status or the use of or specific dose of BRTx on Cox regression analysis. Acute and late toxicity secondary to BRTx was minimal. Conclusions The use of BRTx after primary OTSCC resection with positive/narrow margins ± EBRTx to the neck ± CTx achieves outcomes comparable to traditional treatment of surgery followed by re-resection or EBRTx ± CTx. Morbidity associated with oral cavity EBRTx or secondary resection and reconstruction is thus avoided. Both acute and late toxicity rates are low and compare favourably with other BRTx OTSCC studies. Trial registration Retrospectively registered. https://www.mcgill.ca/rcr-rcn/files/rcr-rcn/2017.06.05_rcn_hn.pdf . Level of evidence 4 Graphical abstract